Zasada analogii w homiliach kierowanych do odbiorcy dziecięcego - Sieradzka-Mruk, Agnieszka (Stylistyka, 2020)
The article presents the principle o f analogy in contemporary Polish Catholic homilies addressed to children. Searching for an analogy between a liturgical text and human life is a very important element o f a homily as a variant o f a sermon, especially a homily to children, because the main aim of this type o f sermon is discovering what a sacred text (the Bibie) says to contemporary man. The article is based on over sixty homilies for children recorded in Cracow Catholic churches in the years 1994-2005. For comparison a similai number o f homilies for adults were used. In the paper different morę or less conventional ways o f reference to human life are discussed. It appears that preachers very often use cognitive schemata, for example so called scripts and scenes, to facilitate understanding. At the level of language these schemata may be a basis of multiword expressions that have a constant function in a given text type and that occur repeatedly in the same situations. These collocations may be characteristic o f a given functional style (register o f language) and o f a given speech genre and a sub-genre, in this case for a homily for children as a speech sub-genre. Searching for analogy seems to fulfill two main functions in homilies: explanation and tic, especiall) in respect to ethical problems, presented on the example of linguistic images o f good and bad deeds, images that are fixed in repeated collocations. It is appropriate to ask why ethical problems in homilies for children are discussed in a schematic and stereotypical way. It may result ffom the genre features of the homily, in which a sacred text is input, or may result ffom an over simplified image o f the child’s world, which preachers have. To explain this problem it would be useful to analyze the language of other types o f sermons and the language o f religious oducation. actualization (reference to the contemporary listener’s situation). Regarding explanation there is a great creativity in the authors o f sermons, whereas actualization is very schematic, especiall) in respect to ethical problems, presented on the example o f linguistic images o f good and bad deeds, images that are fixed in repeated collocations. It is appropriate to ask why ethical problems in homilies for children are discussed in a schematic and stereotypical way. It may result ffom the genre features of the homily, in which a sacred text is input, or may result ffom an over simplified image o f the child’s world, which preachers have. To explain this problem it would be useful to analyze the language of other types o f sermons and the language o f religious oducation.